Respostas
respondido por:
28
Use a fórmula da Geometria Analítica:
![d_{AB}=\sqrt{(x_B-x_A)^2+(y_B-y_A)^2}\\
\\
d_{AB}=\sqrt{(8-5)^2+(9-5)^2}=\sqrt{9+16}=\sqrt{25}=5 d_{AB}=\sqrt{(x_B-x_A)^2+(y_B-y_A)^2}\\
\\
d_{AB}=\sqrt{(8-5)^2+(9-5)^2}=\sqrt{9+16}=\sqrt{25}=5](https://tex.z-dn.net/?f=d_%7BAB%7D%3D%5Csqrt%7B%28x_B-x_A%29%5E2%2B%28y_B-y_A%29%5E2%7D%5C%5C%0A%5C%5C%0Ad_%7BAB%7D%3D%5Csqrt%7B%288-5%29%5E2%2B%289-5%29%5E2%7D%3D%5Csqrt%7B9%2B16%7D%3D%5Csqrt%7B25%7D%3D5)
respondido por:
20
D= raiz de (x2-x1)² + (y2-y1)² ~> d= raiz de (5-8)²+(5-9)² ~> d= raiz de (-3)²+(-4)² ~> d= raiz de 9+16 ~> d= raiz de 25 ~> d=5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás